Talaq outside court under Islamic and Malaysian law in the digitalization era: the impact on iddah and ruju’ - Mohd, Azizah (On İki Levha Yayincilik A. Ş., 2019)
Talaq, in general, refers to the dissolution of a valid marriage through the pronouncement of divorce by the husband. In Islam, talaq is permissible, especially whenever harm is perceived if the marriage continues or the couple fears that they cannot observe the limitation ordained by Allah swt. In Malaysia, the pronouncement of talaq is regulated in the sense that a husband should pronounce talaq in court or otherwise he can be guilty of fine and imprisonment. Such a regulation to a certain extent controls the husband power and authority to pronounce talaq even though the husband’s pronouncement of talaq is still counted as effective if it took place outside court. The rapid growth of digitalization seems to open a flood gate for more pronouncement of divorce outside court. Various electronic means of social communication like Facebook, WhatsApp, email, Instagram, telegram, twitter, etc will become the medium of divorce communication between the husband and the wife. This paper wishes to examine the position of talaq outside Court under Islamic law and the law in Malaysia in this the digitalization era. The examination will include the effect of such pronouncement to iddah and ruju’ especially when the husband is not a knowledgeable person on the rules of Islamic law. Finally, the paper will provide recommendation where necessary especially to improve the law on the pronouncement of talaq in Malaysia where the talaq is uttered through electronic mediums.